SHAREPAD: a collaborative and customisable digital platform for teaching and learning - Kamarudin, Rafidah; Abdullah, Amalia Qistina Castaneda; Zainal Arifin, Mazliyana; Zuraimi, Nur’ain (2025)
This project introduces SHAREPAD, an innovative and interactive online teaching and learning tool developed using the PADLET platform. SHAREPAD addresses common challenges in traditional classroom settings, such as limited real-time collaboration, difficulty accessing resources, and low student engagement. SHAREPAD, which was created as a centralised, multimedia-rich learning environment, enables teachers and students to collaborate and exchange ideas and content across multiple devices and locations. It encourages students’ interaction and creative expression, supporting a variety of educational philosophies with features such as realtime feedback, privacy restrictions, and adjustable layouts. Additionally, SHAREPAD has great marketing potential because subject-specific modules may be created, disseminated, and sold to teachers at all educational levels, from elementary to university, fostering a more cohesive and expansive teaching community.